Differences in serum IgA responses to HIV-1 gp41 in elite controllers compared to viral suppressors on highly active antiretroviral therapy - Nabi, Rafiq; Moldoveanu, Zina; Wei, Qing; Golub, Elizabeth T; Durkin, Helen G; Greenblatt, Ruth M; Herold, Betsy C; Nowicki, Marek J; Kassaye, Seble; Cho, Michael W; Pinter, Abraham; Landay, Alan L; et al. (PloS one, 2017)
Mechanisms responsible for natural control of human immunodeficiency type 1 (HIV) replication in elite controllers (EC) remain incompletely defined. To determine if EC generate high quality HIV-specific IgA responses, we used Western blotting to compare the specificities and frequencies of IgA to HIV antigens in serum of gender-, age- and race-matched EC and aviremic controllers (HC) and viremic noncontrollers (HN) on highly active antiretroviral therapy (HAART). Concentrations and avidity of IgA to HIV antigens were measured using ELISA or multiplex assays. Measurements for IgG were performed in parallel. EC were found to have stronger p24- and V1V2-specific IgG responses than HN, but there were no IgG differences for EC and HC. In contrast, IgA in EC serum bound more frequently to gp160 and gag proteins than IgA in HC or HN. The avidity of anti-gp41 IgA was also greater in EC, and these subjects had stronger IgA responses to the gp41 heptad repeat region 1 (HR1), a reported target of anti-bacterial RNA polymerase antibodies that cross react with gp41. However, EC did not demonstrate greater IgA responses to E. coli RNA polymerase or to peptides containing the shared LRAI sequence, suggesting that most of their HR1-specific IgA antibodies were not induced by intestinal microbiota. In both EC and HAART recipients, the concentrations of HIV-specific IgG were greater than HIV-specific IgA, but their avidities were comparable, implying that they could compete for antigen. Exceptions were C1 peptides and V1V2 loops. IgG and IgA responses to these antigens were discordant, with IgG reacting to V1V2, and IgA reacting to C1, especially in EC. Interestingly, EC with IgG hypergammaglobulinemia had greater HIV-specific IgA and IgG responses than EC with normal total IgG levels. Heterogeneity in EC antibody responses may therefore be due to a more focused HIV-specific B cell response in some of these individuals. Overall, these data suggest that development of HIV-specific IgA responses and affinity maturation of anti-gp41 IgA antibodies occurs to a greater extent in EC than in subjects on HAART. Future studies will be required to determine if IgA antibodies in EC may contribute in control of viral replication.
Keywords: Immunoglobulin G; Male; vysoce aktivní antiretrovirová terapie; HIV obalový protein gp41; HIV Infections; Adult; imunoglobulin G; dospělí; mužské pohlaví; Antibody Affinity; ELISA; HIV infekce; HIV protilátky; HIV Antibodies; Enzyme-Linked Immunosorbent Assay; lidé; ženské pohlaví; Humans; HIV Envelope Protein gp41; afinita protilátek; imunoglobulin A; Antiretroviral Therapy, Highly Active; Female; Immunoglobulin A; lidé středního věku; Middle Aged